Mechanism of Antibacterial Activity via Morphology Change of α-AgVO3: Theoretical and Experimental Insights - De Oliveira, Regiane Cristina; De Foggi, Camila Cristina [UNESP]; Teixeira, Mayara Mondego; Da Silva, Maya Dayana Penha; Assis, Marcelo; Francisco, Eric Mark; Pimentel, Bruna Natalia Alves Da Silva [UNESP]; Pereira, Paula Fabiana Dos Santos; Vergani, Carlos Eduardo [UNESP]; Machado, Ana Lúcia [UNESP]; Andres, Juan; Gracia, Lourdes; et al. (American Chemical Society (ACS), 2017)
The electronic configuration, morphology, optical features, and antibacterial activity of metastable α-AgVO3 crystals have been discussed by a conciliation and association of the results acquired by experimental procedures and first-principles calculations. The α-AgVO3 powders were synthesized using a coprecipitation method at 10, 20, and 30 °C. By using a Wulff construction for all relevant low-index surfaces [(100), (010), (001), (110), (011), (101), and (111)], the fine-tuning of the desired morphologies can be achieved by controlling the values of the surface energies, thereby lending a microscopic understanding to the experimental results. The as-synthesized α-AgVO3 crystals display a high antibacterial activity against methicillin-resistant Staphylococcus aureus. The results obtained from the experimental and theoretical techniques allow us to propose a mechanism for understanding the relationship between the morphological changes and antimicrobial performance of α-AgVO3.
Keywords: antibacterial activity; first-principles calculations; morphologies; photoluminescence; Wulff construction; α-AgVO3